2022
DOI: 10.1186/s12870-021-03396-6
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungus Pseudodidymocyrtis lobariellae KL27 promotes taxol biosynthesis and accumulation in Taxus chinensis

Abstract: Background Taxol from Taxus species is a precious drug used for the treatment of cancer and can effectively inhibit the proliferation of cancer cells. However, the growth of Taxus plants is very slow and the content of taxol is quite low. Therefore, it is of great significance to improve the yield of taxol by modern biotechnology without destroying the wild forest resources. Endophytic fungus which symbiosis with their host plants can promote the growth and secondary metabolism of medicinal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…Those results indicated that MYBs may evolve independently in the different tissues of Taxus to meet the need for the regulation of spatially differential taxol biosynthesis. TcMYB29a was highly expressed in the needles and the roots, which show a similar expression pattern with FLP/MYB88 in Arabidopsis plants, and its expression was highly induced after the fungal elicitor treatment based on the previous study (Cao et al, 2022). Furthermore, the PLACE website predicted that TcMYB29a was induced by ABA, which was verified by qRT-PCR (Figure 10 and Supplementary Figure 1).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Those results indicated that MYBs may evolve independently in the different tissues of Taxus to meet the need for the regulation of spatially differential taxol biosynthesis. TcMYB29a was highly expressed in the needles and the roots, which show a similar expression pattern with FLP/MYB88 in Arabidopsis plants, and its expression was highly induced after the fungal elicitor treatment based on the previous study (Cao et al, 2022). Furthermore, the PLACE website predicted that TcMYB29a was induced by ABA, which was verified by qRT-PCR (Figure 10 and Supplementary Figure 1).…”
Section: Discussionsupporting
confidence: 64%
“…Although ABA has also been evaluated and found to induce taxol biosynthesis in Taxus cell cultures (Zhang and Fevereiro, 2010), its function in the regulation of the taxol biosynthesis is largely unknown. In our current research (Cao et al, 2022), the fermentation broth of an endophytic fungus isolated from T. chinensis could significantly promote taxol accumulation in T. chinensis needles, with a 3.26-fold increase compared to the control. TF-encoding genes, such as MYBs, ERFs, and bHLH, were detected as differentially expressed genes after KL27-FB treatment.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The slow growth rate and scarce resources of Taxus chinensis also limit the application of taxol. Since the isolation of taxol producing endophytes from Taxus chinensis , a new pathway for taxol production has been developed [ 116 , 117 , 118 , 119 ]. The endophytes, especially endophytic funji of Taxus chinensis have high growth rate, low cultivation cost, and are not affected by climate change [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium is a well-known plant pathogenic fungus that causes diseases in a wide range of plants, including fruit crops, vegetables, cereal grains, and ornamentals (Summerell et al, 2003 ; Michielse and Rep, 2009 ; Tembhurne et al, 2017 ; Yang et al, 2022 ; Buttar et al, 2023 ). F. chlamydosporum is a soil-borne pathogen that is widely distributed, has the ability to survive for extended periods in soil, and can act as a facultative parasite, infecting alfalfa (Cao et al, 2022 ). In severe cases, F. chlamydosporum can cause the death of the entire plant by disrupting vital processes such as material absorption and transport, photosynthesis, and material synthesis and transformation, which can inhibit the normal growth of alfalfa.…”
Section: Discussionmentioning
confidence: 99%